Agriculture Productivity Growth in Brazil : Recent Trends and Future Prospects - Arias, Diego; Vieira, Pedro Abel; Contini, Elisio; Farinelli, Barbara; Morris, Michael (World Bank, Washington, DC, 2018)
This report explains about the agriculture productivity growth in Brazil.Agriculture has been an island of success in terms of productivity growth in the last decades compared to other sectors of the Brazilian economy and compared to other country’s agriculture sector.Agriculture productivity growth in recent decades in Brazil has been mainly driven by investments in agriculture innovation, facilitation of sector financing, and trade liberalization. Trade liberalization has shown to be an important factor in the growth of agriculture productivity in recent decades, which can serve as an important experience for other Brazilian economic sectors that remain relatively close to trade. Agriculture productivity has room to grow further, improving productivity of lagging mid-size farmers and regions, reforming agriculture policies towards agriculture financing, agrologistics, and research and development(R&D).Experience within Brazil shows that agriculture productivity can continue to grow without depleting natural capital nor further increasing greenhouse gas (GHG) emissions. Unlike the structural economic transformation of other countries, Brazilian agriculture productivity growth has been a net job creator. Agriculture productivity growth in Brazil can therefore continue its positive upward trend, while being environmentally sustainable, creating jobs, and increasing incomes for the rural poor.The motivation for this report is to explore the evolution and source of the strong agriculture productivity growth that has occurred in Brazil in recent decades, identifying opportunities and challenges for future development of the sector. The goal is to look for opportunities to accelerate agriculture productivity growth, to have an increased impact on sector growth, jobs, environmental sustainability, and poverty reduction, as well as potentially to shed light on lessons that can contribute to efforts to boost productivity in other sectors within Brazil. The report is divided into five sections. Following this introduction, Section two describes the evolution and sources of agriculture productivity growth in recent years; Section three evaluates the contributions of different factors of production, such as natural, human and physical capital; Section four explores the opportunities for further maximizing agriculture growth in Brazil through increases in productivity; and Section five presents conclusions and policy recommendations on how to further maximize agriculture productivity in Brazil while having positive social (poverty reduction and jobs) and environmental impacts.